Penguatan Literasi Sains Melalui Field Trip Ekosistem Lahan Gambut: Perspektif Konseptual: (Strengthening Scientific Literacy Through Peatland Ecosystem Field Trips: a Conceptual Perspective) - Patmawati , Kiki; Hariyadi , Bambang; Yusnaidar , Yusnaidar (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
Scientific literacy is an essential competency in 21st-century Natural Science (IPA) learning. However, science learning at the junior high school level is still dominated by a textual approach and minimal real-world environmental context, so that the development of students' scientific literacy is not optimal. This article aims to conceptually examine the strengthening of scientific literacy through field trip learning in peatland ecosystems in the science subject of grade VII of junior high school. The writing method used is a conceptual study (conceptual paper) with literature sources in the form of textbooks, accredited national journals, and reputable international journals. The literature was selected based on its relevance to scientific literacy, field trip learning, and peatland ecosystems. The analysis technique was carried out through synthesis and concept mapping. The results of the study indicate that field trip learning in peatland ecosystems has the potential to be a contextual learning approach that is able to integrate knowledge, scientific processes, and scientific attitudes, thereby strengthening the scientific literacy of junior high school students. This article is expected to serve as a theoretical basis for the development of environment-based science learning. Abstrak. Literasi sains merupakan kompetensi esensial dalam pembelajaran Ilmu Pengetahuan Alam (IPA) abad ke-21. Namun, pembelajaran IPA di tingkat SMP masih didominasi pendekatan tekstual dan minim konteks lingkungan nyata, sehingga pengembangan literasi sains siswa belum optimal. Artikel ini bertujuan untuk mengkaji secara konseptual penguatan literasi sains melalui pembelajaran field trip pada ekosistem lahan gambut dalam mata pelajaran IPA kelas VII SMP. Metode penulisan yang digunakan adalah kajian konseptual (conceptual paper) dengan sumber literatur berupa buku teks, jurnal nasional terakreditasi, dan jurnal internasional bereputasi. Literatur dipilih berdasarkan relevansi dengan literasi sains, pembelajaran field trip, dan ekosistem lahan gambut. Teknik analisis dilakukan melalui sintesis dan pemetaan konsep. Hasil kajian menunjukkan bahwa pembelajaran field trip ekosistem lahan gambut berpotensi menjadi pendekatan pembelajaran kontekstual yang mampu mengintegrasikan pengetahuan, proses sains, dan sikap ilmiah sehingga memperkuat literasi sains siswa SMP. Artikel ini diharapkan dapat menjadi landasan teoretis bagi pengembangan pembelajaran IPA berbasis lingkungan.